DNA content and MHC class II antigen expression in malignant melanoma: clinical course. Issue 10 (October 1988) - Zaloudik, J; Moore, M; Ghosh, A K; Mechl, Z; Rejthar, A
Abstract : To assess the clinical value of two comparatively new properties (DNA content and MHC class II antigen expression (HLA-DR, DP, DQ) of melanoma cells) which have been independently reported to reflect the outlook for patients with malignant melanoma, we investigated retrospectively 50 stage I nodular melanomas in two comparably homogeneous groups of 23 and 27 patients, the course of whose disease differed at five years. Flow cytometry and immunohistology were used on paraffin wax embedded archival material for the analysis of DNA ploidy and detection of class II antigens, respectively. A close association was found between class II antigen expression, detected by monoclonal antibody CR3/43 (antimonomorphic DR, DP, DQ) present in 23 of 50 (46%) melanomas and unfavourable clinical course (p less than 0.005, by log rank test), but no such association was found for DNA ploidy. It is suggested that immunohistology for MHC class II antigen expression may help to predict the behaviour of nodular melanomas whereas the prognostic value of DNA ploidy is more limited. The finding that class II positive cells are found predominantly in melanomas with a substantially increased risk of metastases has implications both for concepts of tumour heterogeneity and host immunity.